If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13x + 38 = 6x + -25 Reorder the terms: 38 + -13x = 6x + -25 Reorder the terms: 38 + -13x = -25 + 6x Solving 38 + -13x = -25 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 38 + -13x + -6x = -25 + 6x + -6x Combine like terms: -13x + -6x = -19x 38 + -19x = -25 + 6x + -6x Combine like terms: 6x + -6x = 0 38 + -19x = -25 + 0 38 + -19x = -25 Add '-38' to each side of the equation. 38 + -38 + -19x = -25 + -38 Combine like terms: 38 + -38 = 0 0 + -19x = -25 + -38 -19x = -25 + -38 Combine like terms: -25 + -38 = -63 -19x = -63 Divide each side by '-19'. x = 3.315789474 Simplifying x = 3.315789474
| x^2-kx+1=0 | | 2x+5=2(x-1) | | 2.2x-5=8x+3 | | 3(b+4)=(b+4)2 | | -4x-7=12 | | =2x-8xy | | 4/21-h/24 | | 2x+2-2(-5x-5)=2(x-3) | | 6a-4b+a-5b= | | 6t+16=9 | | 1/5/1 | | (3/4)t+(1/8)=(3/4)(t+8) | | m/4=9/5 | | -1/5/-1 | | 6+16=9 | | 20=-2v | | -2x=-2+5 | | 0=-6n-2n | | 2x+9-2=31 | | 4.4x+64=19.36+8x | | x+(3x^1/2)-10 | | 2+6d-4= | | 9/11*14.4=-12 | | 4(x+2)-6=2x | | -4=6b-4+2b | | 9/2d=27 | | m/4=h/24 | | s+2/1/2s+10=31 | | 9(2/3) | | -x-24=-8 | | 20+5n=6n-3(n-4) | | (x^7z^5)/(x^6z) |